The Factors affecting Organizational Citizenship Behavior: Role of Organizational Commitment and Job Satisfaction - Muhammad Iqbal Baihaqi; Heru Setiawan; Dinda Lucyana Romli (Journal of Applied Management and Business, 2023)
This research was conducted to determine how much influence job satisfaction and organizational commitment have on the (OCB). The methodology that used in this study is a quantitative research method with descriptive analysis and verification analysis approaches. The sample used was 42 employees. The results showed that job satisfaction and organizational commitment had a significant effect on (OCB) which. Job satisfaction has a significant effect on (OCB), while organizational commitment has a significant effect on Organizational Citizenship Behavior (OCB). The results showed that organizational commitment contributes more to Organizational Citizenship Behavior (OCB) than job satisfaction.